Efek motivational interviewing dan kelas edukasi gizi berbasis instagram terhadap perubahan pengetahuan healthy weight loss dan kualitas diet mahasiswi obesitas - Ira Mulyani; Fillah Fithra Dieny; Ayu Rahadiyanti; Deny Yudi Fitranti; A Fahmy Arif Tsani; Etisa Adi Murbawani (Jurnal Gizi Klinik Indonesia, 2020)
Effect of motivational interviewing and nutrition education class based on instagram for change healthy weight loss knowledge and diet quality in obese female studentsBackground: Obesity is a health problem that has a serious impact on women. Instagram is one of the media for nutrition education that can present healthy messages effectively and motivational interviewing can improves intrinsic motivation to changes in behavior. Objective: To analyze the effects of motivational interviewing and nutrition education class on changes in healthy weight loss knowledge and diet quality. Methods: This study used a quasi-experimental design with the pre-post test control group. The sample consists of 40 female students obesity were divided into three groups, control group (K); intervention group 1 with motivational interviewing and nutrition education class (P1); intervention group 2 only nutrition education class (P2). The nutrition education class based on instagram was given for thirty days and motivational interviewing was given 4 times with a duration of 15-45 minutes. Changes in healthy weight loss knowledge were assessed by pre-test and post-test questionnaire, while diet quality was assessed by Diet Quality Index-International (DQI-I). Results: There was a significant difference between healthy weight loss knowledge in the three groups. There were significant differences on sub-components of the adequacy of staple food (p=0.026), fiber (p=0.026), protein (p=0.006), total fat intake (p=0.009), saturated fat intake (p=0.024), sodium intake (p=0.016), energy intake (p=0.000), and carbohydrate intake (p=0.002) in the three groups. Conclusions: Motivational interviewing and nutrition education class based on instagram could increase the healthy weight loss knowledge and reduce staple food intake, total fat intake, saturated fat intake, sodium intake, energy intake, and carbohydrate intake in obese women.